Adverse events linked with the use of chimeric and humanized anti‐CD20 antibodies in children with idiopathic nephrotic syndrome. (25th March 2018) - Bonanni, Alice; Calatroni, Marta; D'Alessandro, Matteo; Signa, Sara; Bertelli, Enrica; Cioni, Michela; Di Marco, Eddi; Biassoni, Roberto; Caridi, Gianluca; Ingrasciotta, Giulia; Bertelli, Roberta; Di Donato, Armando; et al.
Abstract : Aims: Anti‐CD20 antibodies are increasingly being used to treat idiopathic nephrotic syndrome (INS) in children. While they may allow steroid and calcineurin inhibitor withdrawal, repeated infusions of anti‐CD20 antibodies are often required to maintain remission. Data on their potential toxicity in INS are needed, to consider repeated infusions. Methods: We investigated the side effects associated with the use of rituximab (a chimeric antibody; 130 patients) and ofatumumab (a humanized antibody; 37 patients) in children with INS (steroid‐dependent and steroid/calcineurin inhibitor‐dependent disease) treated at a national referral centre over a 9‐year period (400 treatments; follow‐up 1–9 years). Results: Infusion reactions were mainly absent in children with steroid‐dependent disease. Rash, dyspnoea, fever, cough and itchy throat (5% and 18% following rituximab and ofatumumab infusion, respectively) were resolved by using premedication with salbutamol. Other short‐term reactions (up to 3 months), including arthritis (2%) and lung injury (1%), were more common with rituximab. Infections were observed 3–9 months following infusion, were similarly common in the two groups and resolved with targeted therapies [antibiotic, fluconazole, immunoglobulins (Igs), etc.]. The number of circulating CD19/20 cells fell to 0 at month 1 and were reconstituted at month 3; circulating IgG antibodies remained within the normal range for 1 year. Tetanus and hepatitis B virus immunization was not modified by either treatment; Epstein–Barr virus and John Cunningham virus activation markers were occasionally observed. Conclusion: Overall, the toxicity of anti‐CD20 monoclonal antibodies was limited to post‐infusion side effects in children with more complex disease. The relatively safe profile of anti‐CD20 antibodies supports their use as steroid‐sparing agents in children with INS.